Antioxidant Activities and Thin Layer Chromatographic Analysis of Aqueous Extract of Tubers of Drynaria quercifolia (L).J.Sm - Sivaraj, Chandrasekaran; Aashinya, Y; Sripriya, Ramalingam; Arumugam, Perumal (Free Radicals and Antioxidants)
Objectives: The aim of the study was to investigate phytochemical constituents, free radical scavenging activities and antimicrobial activities of the aqueous extract of tubers of Drynaria quercifolia. Materials & Methods: The qualitative and quantitative analyses were carried out for the aqueous extract using standard procedures. The antioxidant activities were carried out by DPPH free radical, ABTS•+ radical cation, OH• radical, NO• radical scavenging assays as well as Fe3+ reducing power and phosphomolybdenum reduction assays. Results: The tubers of D. quercifolia in aqueous extract showed good radical scavenging as well as reducing power activities. The major phytochemicals such as phenols and flavonoids were estimated as 4.29±1.23 and 24.56±0.86 μg/mL respectively. Conclusion: The aqueous extract of tubers of D. quercifolia possesses significant antioxidant activities.
Keywords: Drynaria quercifolia; Phenols; Flavonoids; Antioxidant; Dot-blot assay